A Review of the Role of Workplace Spirituality and Organizational Citizenship Behavior in Enhancing Corporate Sustainability: An Underpinning Role of Stern and Dietz's Value Model. (May 2022) - Hafeez, Muhammad; Yasin, Ida Md.; Zawawi, Dahlia; Qureshi, Naveed Akhtar; Hussain, Syed Talib; Arif, Muhammad
Organizations are under pressure to explore innovative sustainability practices that will enable organizations to handle the deteriorating issues of biodiversity and social inequality. Stern and Dietz' model offered a set of values with which organizations can create sustainability. This study's main purpose was to explore how Stern and Dietz' model underpin the various dimensions of workplace spirituality and organizational citizenship behavior to accomplish corporate sustainability. To achieve the objective of the study, the previous literature was reviewed to construct a conceptual framework. This conceptual model is comprised of three phases egoistic, social altruistic, and biospheric. Based on prior literature, various dimensions of workplace spirituality and organizational citizenship behavior were underpinned to accomplish corporate sustainability. Even though this concept sets out basic guidelines. However relevant knowledge should be regarded in order to reconcile these steps in different instances. This article provides a systematic review of the Stern and Dietz value model to achieve various aspects of organizational sustainability. A constructive framework was developed to create corporate sustainability by incorporating workplace spirituality and organizational citizenship behavior into the context of the Stern Dietz' value model. Theoretical and practical implications are also discussed in this study.